Academic freedom and the eye of power: the politics and poetics of open enclosures. Issue 2 (3rd May 2016) - Ryan, Kevin
Abstract : Transparency is both a powerful idea and a technology of power associated with accountability, justice and democracy, which opposes the secretive and shadowy power of surveillance wielded by states and corporations. This article examines surveillance and transparency not as a dichotomy but as a constitutive relation in the field of academia, focusing specifically on ranking and rivalry in the context of competitive performance. Transparency-as-openness (open access platforms) is enmeshed in enclosures assembled from (self-) surveillance, personal data, public institutions and private enterprise. The analysis pays particular attention to how altmetrics and credibility metrics – used to enhance personal prestige and professional standing – reinforce the neo-liberalisation of higher education. The article concludes by engaging critically with the politics and poetics of open enclosures with a view to re-imagining the practice of academic freedom.